A pilot case crossover study of the use of padded headgear in junior Australian football - Catherine Willmott; Jonathan Reyes; Jack VK Nguyen; Andrew McIntosh; Jennifer Makovec-Knight; Michael Makdissi; Patrick Clifton; Peter Harcourt; Biswadev Mitra (Concussion)
Aim: To explore soft-shell padded headgear (HG) use, player behavior and injuries associated with HG in junior Australian football. Methods: Prospective case-crossover with head impact measurement, injury surveillance and video review. Results: 40 players (mean age: 12.43 years, standard deviation: 1.36) across 15 matches were observed. Frequency of head/neck (p = 0.916) or body (p = 0.883) contact events, and match incidents were similar between HG and no HG conditions. Without HG, females had higher frequency of body contacts compared with males (p = 0.015). Males sustained more body contacts with HG than without HG (p = 0.013). Conclusion: Use of HG in junior football was not associated with injury or head contact rate. Associations between HG use and body contact may differ across sexes. (ID: ACTRN12619001165178).